PERAN KOMITE NASIONAL PEMUDA INDONESIA SEBAGAI SARANA PENDIDIKAN POLITIK PEMUDA (STUDI KASUS KNPI KECAMATAN SAMARINDA SEBERANG) - Pahlepi, Sayid Muhammad Reza (Jurnal Administrative Reform, 2022)
The research findings show the role of KNPI as a means of political education through activities such as conducting board orientation, leadership regeneration, leadership training, conducting general election discussions, and cooperating with other organizational partners and the government. Forms of implementing political education include helping local governments and socializing politics, especially regarding crucial issues, Providing political education to youth and KNPI cadres, Samarinda Seberang District, Socialization of Simultaneous Regional Head Elections Obstacles faced in becoming a means of political education are obstacles in educating the political community and KNPI cadres in Samarinda Seberang District and obstacles in funding activities. Keywords : role, education, politic, KNPI